Hak dan Kewajiban Suami Istri dalam Kitab ‘Uqūd al-Lujayn dan Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan - Lutfiatul Khasanah (Institut Agama Islam Negeri (IAIN) Kediri, 2017)
A matrimony causes law effects for husband and wife called the rights and obligations. A husband and wife each have the right and obligation in marriage. Book ‘Uqūd al Lujayn by Shaykh Muhammad Bin Umar Al-Nawawī Al-Bantanī constituting book that works through marriage and still frequently be assessed at several boarding houses or pondok pesantren in Indonesia. Indonesia which constitutes as a law based country has managed laws on marriage, namely Undang-Undang Number 1 Year 1974 about marriage to know the right and obligations which correspond to orders in Islam and not rule out Indonesian marriage Law. This research is arranged utilized answers severally problem formula by using library research with qualitative method and descriptive analytic which is the researcher tries to word aught material with intent fact finding by analyzing what do be equal to as effort to solve problems . Data collecting is utilized to methodic library material via written texts and also soft copy edition and analyzed by content analyses and comparisons. Based on the observational result, researcher concludes that: (1) Books ‘ Uqūd al Lujayn in managing rights of husband and wife which positioning husband rights upon as level as higher as wife. (2) the right and obligation equations of husband and wife in book ‘ Uqūd al Lujayn and Number Law 1 Year 1974 Connubial are both husband and wife have to be good and glorious, husband as patriarch, husband mandatorying to give wife earnings, wife as housewife that mandatory manage housewifery with all the best and mandatory husband and wife mutually loves, faithful and helping. Meanwhile difference of both lays in rights arrangement and wife husband position, negligence sanction in going liabilities and wife permit liabilities to husband. (3 ) Basic Principle that become difference concept base rights balance and wife husband position in book ‘Uqūd al Lujayn and Number Law 1 Year 1974 connubial are that book footing ‘Uqūd al Lujayn on Q.S Al Baqarah (2 ): 228, Q. S al Baqarah (2 ): 228 and hadis is Prophets. Meanwhile Number Law footing 1 Year 1974 connubial on jender’s equation.